2015
DOI: 10.1371/journal.pcbi.1004255
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Voltage Gating of Providencia stuartii Porins at Atomic Level

Abstract: Bacterial porins are water-filled β-barrel channels that allow translocation of solutes across the outer membrane. They feature a constriction zone, contributed by the plunging of extracellular loop 3 (L3) into the channel lumen. Porins are generally in the open state, but undergo gating in response to external voltages. To date the underlying mechanism is unclear. Here we report results from molecular dynamics simulations on the two porins of Providenica stuartii, Omp-Pst1 and Omp-Pst2, which display distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
(72 reference statements)
3
9
1
Order By: Relevance
“…Calculation of the electrostatic potential along the Omp-Pst2 channel furthermore suggests a facilitated transport of cations from the intracellular to the extracellular side of the porin ( Fig. 1 J and L), in line with recent MD simulations based on the structure (15). We note that as in Omp-Pst1 crystals, no contact is observed between intracellular turns of Omp-Pst2, and a cavity is apparent at the center of the trimeric complex.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Calculation of the electrostatic potential along the Omp-Pst2 channel furthermore suggests a facilitated transport of cations from the intracellular to the extracellular side of the porin ( Fig. 1 J and L), in line with recent MD simulations based on the structure (15). We note that as in Omp-Pst1 crystals, no contact is observed between intracellular turns of Omp-Pst2, and a cavity is apparent at the center of the trimeric complex.…”
Section: Resultssupporting
confidence: 89%
“…The electrostatic potential profile calculated along the channel of Omp-Pst1 indicates mild anion selectivity ( Fig. 1L), in line with electrophysiology measurements and with molecular dynamics (MD) simulations based on this structure (15). Nevertheless, the Omp-Pst1 channel features more charged residues than E. coli porins (48%, 35%, and 20% more charged residues than OmpF, OmpC, and PhoE, respectively), suggesting higher translocation selectivity.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…stuartii predominantly expresses Omp-Pst1, and it was proposed that Omp-Pst1 is the major porin of the bacterium [40]. Electrophysiology measurements revealed that Omp-Pst2 is highly cation-selective and prone to voltage-gating (critical voltage Vc = 20–90 mV), whereas Omp-Pst1 channel gates normally (Vc > 199 mV), is mildly anion selective and comparatively more permissive to β-lactam antibiotics [40,41]. MD simulations suggested that Omp-Pst2 atypical voltage-gating behaviour is asymmetric and triggered by the influx of cations from the extracellular to the periplasmic side of the porin.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the biological function of these channel properties, various hypotheses are put forward. In particular, this may be due to the closing of the channels of improperly incorporated proteins and may also be the protective (as the medium pH decreases) or even regulatory transport function of porins (e.g., in proteins with a very low critical channel closure voltage, Vc) [15, 16]. However, all the proposed explanations are not sufficiently convincing and, perhaps, this property may be considered only as an unusual artifact [17].…”
Section: Introductionmentioning
confidence: 99%